Woven into the tapestry : how five women shaped Ethiopian history - Tekeste Negash (Los Angeles: : TSEHAI Publishers & Distributors, 2016)
Woven into the Tapestry: How Five Women Shaped Ethiopian History offers a rich combination of history and art celebrating the contributions of five extraordinary women: Queen Ahyewa, Makeda (the Queen of Sheba), Queen Eleni, Queen Taytu, and the British activist Sylvia Pankhurst. Each of these determined leaders lived through crucial moments in Ethiopian history as they intersected with larger world events, from the spread of Christianity to the Second World War, and each was instrumental in shaping Ethiopia s historical trajectory in ways previously neglected by historians. This book demonstrates the lasting impacts of policies adopted, implemented, and orchestrated by these powerful women who dedicated themselves to the cause of a nation when they were needed most. Joining the words of emeritus professor in history Tekeste Negash, author of several books on Ethiopian culture and history, with the lush tapestries of art historian and tapestry artist Berit Sahlstrm̲, this book brings to life Five Women and takes readers on a journey through the long history of Ethiopia, a nation that has forged and maintained its independence in the face of often staggering adversity. Beginning with Ahyewa s fateful decision to adopt Christianity as the faith of her people, through the rise of a nation under the legendary Queen of Sheba, the building of an empire through Eleni and Taytu s fight for survival against the onslaught of European colonialism during the Scramble for Africa, to Pankhurst s tireless advocacy for postwar independence, this book spans centuries while remaining focused on the immense contributions of five truly remarkable women.